2013
DOI: 10.1016/j.neuropsychologia.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of neural activity in an integration of visual and contextual information in an esthetic preference task

Abstract: While viewing works of art in galleries, we evaluate them by integrating at least two types of information: their visual properties (e.g., colors, symmetry, and proportion) and contextual information accompanying them (e.g., titles and names of artists). How rapidly the brain integrates visual and contextual information of artworks remains to be investigated. Using electroencephalography (EEG), we investigated neural activity when subjects with no professional experience in art viewed images of sculptures (mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 33 publications
6
47
0
Order By: Relevance
“…In the museum, visitors with an aesthetic orientation encounter genuine artworks. Authenticity is an important factor increasing the monetary value [28] and aesthetic evaluation of art [30]. It remains unclear, however, whether the physical context, the authenticity of the artwork, or an interaction between them determines the enhanced art experience in the museum.…”
Section: Discussionmentioning
confidence: 99%
“…In the museum, visitors with an aesthetic orientation encounter genuine artworks. Authenticity is an important factor increasing the monetary value [28] and aesthetic evaluation of art [30]. It remains unclear, however, whether the physical context, the authenticity of the artwork, or an interaction between them determines the enhanced art experience in the museum.…”
Section: Discussionmentioning
confidence: 99%
“…While some effects of context on art appreciation have been discussed and demonstrated (Brieber, Nadal, & Leder, 2015;Brieber, Nadal, Leder, & Rosenberg, 2014;Gartus & Leder, 2014;Gerger, Leder, & Kremer, 2014;Hagtvedt & Patrick, 2011;Kirk, 2008;Kirk, Skov, Hulme, Christensen, & Zeki, 2009;Marković, 2012;Noguchi & Murota, 2013;Swami, 2013), the actual processes that cause contextual differences are yet unclear. Therefore, in addition to traditional rating scales, in the present study we employed the measurement of eyemovements to study whether the perception of artworks differs with context, or even interacts with different kinds of contexts.…”
Section: Art and Contextmentioning
confidence: 99%
“…First, it is well established that the perception of any object whatsoever is not context-free, and that contextual information is stored in memory together with object-related information, facilitating subsequent object recognition (Bar, 2004;Engel, Maye, Kurthen, & König, 2013;Oliva & Torralba, 2007). Second, it has been shown that verbal and visual semantic contextual framing have a profound influence on art appreciation, as well as the underlying neural processes (Gartus & Leder, 2014;Kirk, Skov, Hulme, Christensen, & Zeki, 2009;Noguchi & Murota, 2013). Third, the few studies comparing art appreciation of original works exhibited at museums and their reproductions in the laboratory found differences regarding the appreciation of art.…”
Section: Introductionmentioning
confidence: 99%